2014
DOI: 10.1155/2014/342693
|View full text |Cite
|
Sign up to set email alerts
|

Autoantibodies Targeting AT1 Receptor from Patients with Acute Coronary Syndrome Upregulate Proinflammatory Cytokines Expression in Endothelial Cells Involving NF-κB Pathway

Abstract: Our study intended to prove whether agonistic autoantibodies to angiotensin II type 1 receptor (AT1-AAs) exist in patients with coronary heart disease (CHD) and affect the human endothelial cell (HEC) by upregulating proinflammatory cytokines expression involved in NF-κB pathway. Antibodies were determined by chronotropic responses of cultured neonatal rat cardiomyocytes coupled with receptor-specific antagonists (valsartan and AT1-EC2) as described previously. Interleukin-6 (IL-6), vascular cell adhesion mole… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 52 publications
0
17
0
1
Order By: Relevance
“…EPCs may be a potential therapeutic target for vascular repair and regeneration, due to their strong capacity for proliferation and differentiation (20). However, studies have reported that EPCs may be damaged by Ang II and there is evidence that Ang II upregulates the levels of pro-inflammatory cytokines (including IL-6, monocyte chemoattractant protein-1 and VCAM-1) via the type 1 Ang II receptor, which may deteriorate the atherosclerotic inflammatory response (21,22). Consistent with previous studies, the results of the present study suggested that cell proliferation and migration were decreased by Ang II, and it was demonstrated that 1.0 µM Ang II stimulated ROS production to increase EPC senescence, and increased the expression of ICAM-1 and VCAM-1, two adhesion molecules of EPCs.…”
Section: Discussionmentioning
confidence: 99%
“…EPCs may be a potential therapeutic target for vascular repair and regeneration, due to their strong capacity for proliferation and differentiation (20). However, studies have reported that EPCs may be damaged by Ang II and there is evidence that Ang II upregulates the levels of pro-inflammatory cytokines (including IL-6, monocyte chemoattractant protein-1 and VCAM-1) via the type 1 Ang II receptor, which may deteriorate the atherosclerotic inflammatory response (21,22). Consistent with previous studies, the results of the present study suggested that cell proliferation and migration were decreased by Ang II, and it was demonstrated that 1.0 µM Ang II stimulated ROS production to increase EPC senescence, and increased the expression of ICAM-1 and VCAM-1, two adhesion molecules of EPCs.…”
Section: Discussionmentioning
confidence: 99%
“…miR-145 has been investigated in some other human diseases, such as malignancy [28], diabetes [29] and also other cardiovascular disease [30]. The functional role of miR-145 in the diseases above has been uncovered.…”
Section: Discussionmentioning
confidence: 99%
“…Ang II also has prooxidant effects and induces a decrease in NO bioavailability [ 5 , 13 ]. Upon binding AT1R, it triggers the signaling pathway that activates NADH oxidase to produce O 2 ∙− [ 4 ], increasing the intracellular concentration of this radical ion, and overcoming cellular antioxidant mechanisms (superoxide dismutase, catalase, and glutathione peroxidase).…”
Section: Discussionmentioning
confidence: 99%
“…The presence of ROS is detected by proteins sensitive to the redox status of the cell; in turn, these proteins activate AKT (Protein kinase B), MAPKs (mitogen-activated protein kinases), and NF-κB (Nuclear factor kappa B) [ 7 , 8 , 9 , 10 ], triggering inflammation and promoting the synthesis of IL-1β, IL-6, TNF-α, C reactive protein, E-selectin, ICAM-1 (Intercellular Adhesion Molecule 1), VCAM-1 (Vascular cell adhesion protein 1), and MCP-1 (Monocyte chemoattractant protein-1), among other molecules [ 11 , 12 , 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%